Intervenciones de enfermería en el paciente con procedimientos quirúrgicos ambulatorios - Burbano Fernández, Maritza Tatiana (2026)
Outpatient surgical procedures are medical interventions performed in a hospital or clinic setting, designed so that the patient does not require prolonged hospitalization. For this reason, this research aims to describe nursing interventions in patients undergoing outpatient surgical procedures through a systematic review, requiring the use of a methodology based on a qualitative approach, which analyzed the results of previous studies on nursing interventions in patients undergoing outpatient surgical procedures, using the PRISMA methodology to structure the literature review, including an exhaustive search with rigorous selection, which allowed for detailed data through critical evaluation, ensuring rigor in the reporting of findings. Among the main results within nursing interventions, the following stand out: individualized preoperative education, assessment of emotional state, preparation of the surgical environment, pain control through analgesic protocols, prevention of complications such as nausea, vomiting, and infections, postoperative telephone follow-up, and clear instructions on self-care at home. These actions, implemented in a timely manner, contribute to a safe recovery, reduce readmissions, and strengthen the quality of care in the outpatient model. It was concluded that emotional support, tailored education, and constant communication with the patient influence the reduction of preoperative anxiety, as well as adherence to postoperative care, improving clinical outcomes and safe outpatient recovery.